Speech of Sir Wm. Molesworth, Bart., M.P., in the House of Commons, on Tuesday, 25th July,1848, on colonial expenditure and government (the Association [etc.], 1849)
In pamphlet volume with covertitle : Tracts of the Liverpool Financial Reform Association.